2013
DOI: 10.1590/s1516-89132013000600005
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties of some filamentous green algae (Chaetomorpha Genus)

Abstract: The antioxidant activity and the contents of total phenolics and flavonoids were quantified in the methanolic extracts of four Chaetomorpha species including C. aerea, C. crassa, C. linum and C. brachygona.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 21 publications
(18 reference statements)
3
13
0
4
Order By: Relevance
“…Previous studies have shown the antioxidant activity to be higher in solvents with lower polarity as they dissolve higher molecular weight phenols giving the extract stronger antioxidant effects. 29 The observed negative correlation between the total phenolic/flavonoid content with the antioxidant IC 50 value is consistent with a research by Farasat et al 30 which shows that the higher the phenolic/flavonoid content, the lower the IC 50 value and hence the higher the antioxidant activity per gram of extract. Other studies have confirmed the direct relationship between phenolic content and antioxidant activity 28 and this lends credence that the observed antioxidant activity in the studied plants may be largely due to the phenolic content in the extracts.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have shown the antioxidant activity to be higher in solvents with lower polarity as they dissolve higher molecular weight phenols giving the extract stronger antioxidant effects. 29 The observed negative correlation between the total phenolic/flavonoid content with the antioxidant IC 50 value is consistent with a research by Farasat et al 30 which shows that the higher the phenolic/flavonoid content, the lower the IC 50 value and hence the higher the antioxidant activity per gram of extract. Other studies have confirmed the direct relationship between phenolic content and antioxidant activity 28 and this lends credence that the observed antioxidant activity in the studied plants may be largely due to the phenolic content in the extracts.…”
Section: Discussionsupporting
confidence: 90%
“…On contrary, Vimala and Poonghuzhali (2015) reported only 1.38 µg/g of carotenoid content in Ulva reticulata Forsskal. Similar results were observed in Chaetomorpha sp., (6.743±0.1 to 18.17±2.2) by Farasat, Nejad, Seyed, and Namjooyan (2013) and Codium adharens C. Agardh (38.5 µg/g) by Seenivasan et al (2013). The high content of these phytochemicals could exp lain its high radical scavenging activity.…”
Section: Results and Discussion Total Phenol Flavonoi D And Carotenomentioning
confidence: 90%
“…These compounds are widely distributed in plants and are known to be potent antioxidants. Therefore, these metabolites may help slugs in the intertidal zone with a high level of oxidative stress induced by desiccation during low tides 30 , 31 . Indeed, genistein showed antimutagenic effects with DNA damage agents at a concentration of 10 μM 32 .…”
Section: Discussionmentioning
confidence: 99%